2009
DOI: 10.1007/s00265-009-0789-3
|View full text |Cite
|
Sign up to set email alerts
|

Do bumble bee queens choose nest sites to maximize foraging rate? Testing models of nest site selection

Abstract: We proposed "Foundress-Max" hypothesis that a bumble bee foundress chooses her nest site to maximize her energy intake rate from nectar. To examine the hypothesis, we estimated the maximum energy intake rate at each site in the study area, and compared the distribution of the maximum energy intake rates with those of actual nest sites. We also calculated rank correlations of the maximum energy intake rate with the number of nest-searching foundresses at 54 sites. The nest locations supported the Foundress-Max … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…(), who found that floral availability of agricultural field margins was not correlated with abundance of nest‐searching queens. In contrast, floral resources have been found to predict nest‐searching queens (although only in the early morning) and also the location of actual nests of B. ardens (Suzuki et al ., ). However Suzuki et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(), who found that floral availability of agricultural field margins was not correlated with abundance of nest‐searching queens. In contrast, floral resources have been found to predict nest‐searching queens (although only in the early morning) and also the location of actual nests of B. ardens (Suzuki et al ., ). However Suzuki et al .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore locations with ample spring flowering plants might be the most suitable (Fye & Medler, ; Holm, ), and in support of this Suzuki et al . () found a positive relationship between floral availability and number of nest‐searching queens in Bombus ardens , but only during the early morning when it was cool; later in the day nest‐searching queens were found far from flowers. They subsequently found that nests tended to be located in flower‐rich areas, but only six nests were detected…”
Section: Introductionmentioning
confidence: 98%
“…We focused instead on offspring production by colonies placed into the field. Nest establishment is an important factor in determining population density and persistence within the landscape (Goulson et al 2010), and since the foundress queen alone forages to support the nascent colony, it might be a period when colonies are particularly sensitive to resource limitation (Suzuki et al 2009). By placing colonies of standard size directly into the field, we also filtered out variation related to colony establishment.…”
Section: Discussionmentioning
confidence: 99%
“…The high variation in pollinator abundance observed near natural habitat (Fig. 3) could be attributable to differences in the assemblage of native plants present in natural areas, as certain native plants may provide more adequate floral resources or better nesting conditions than others (Suzuki et al. 2009).…”
Section: Discussionmentioning
confidence: 99%